Misconceptions in radical numbers in secondary school mathematics - Ozkan, Ayten (SCIENCEPARK SCI, ORGANIZATION & COUNSELING LTD, 2019)
The aim of this study was to determine misconceptions of the radicals of the high school students that attend ninth class. The samples of study consist of the students of a Secondary School in Istanbul, Turkey. Some sample questions are asked to related students to understand the misconceptions. According to the result of the study, it is seen that the students have misconceptions about radicals. It is observed that the students have superficial information about deep- rooted numbers and memorise the definition of deep-rooted numbers and try to use them in their mistakes. Some solutions are recommended to those students to overcome such difficulties.
Keywords: Mathematics education; radicals; misconceptions; Education & Educational Research